PENGARUH ENVIRONMENTAL UNCERTAINTY DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE - Fadya Ameliani Aulia, - (2022)
This study aims to analyze the effect of environmental uncertainty and corporate social responsibility on tax avoidance. The population of this study is the manufacture of companies listed on the Indonesia Stock Exchange (IDX) in 2019 -2021. The sampling method used purposive sampling and obtained 46 companies as research samples. The research method used is descriptive research method with a quantitative approach with data analyzed using multiple linear regression. The program used in the calculation and data processing is SPSS Statistics 25. The test results show that environmental uncertainty partially or individually has positive effect on tax avoidance. Meanwhile, corporate social responsibility has no effect on tax avoidance.